Characterization of the Complete Mitochondrial Genome of Kaloula mediolineata (Microhylidae, Anura) and Its Phylogenetic Analysis - Thu-Thao Thi Huynh; Minh Trong Quang; Hoang Danh Nguyen (Biomedical and Biotechnology Research Journal)
Background: Kaloula mediolineata is an ecologically important frog species found in the deciduous dipterocarp forests of Indochina, which are currently threatened by habitat loss and human exploitation. Despite its significance, the mitochondrial genome of K. mediolineata has not been characterized. Methods: In this study, we sequenced and annotated the complete mitochondrial genome of K. mediolineata for the first time. Phylogenetic analyses were conducted to determine the taxonomic status and evolutionary relationships of K. mediolineata within the Kaloula genus. Results: The mitochondrial genome of K. mediolineata is a circular DNA molecule of 16,812 base pairs, encoding 37 genes, including 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes, and a control region. Phylogenetic analyses revealed that K. mediolineata is most closely related to Kaloula conjuncta, confirming a sister relationship within the Kaloula genus. Conclusions: This study provides valuable genetic information about the molecular characteristics and evolutionary relationships of Kaloula species, which can inform future research and conservation efforts for this threatened frog species.